2021
DOI: 10.1016/j.lanwpc.2021.100279
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a parenting programme to reduce violence in a cash transfer system in the Philippines: RCT with follow-up

Abstract: Background: Parenting interventions and conditional cash transfer (CCT) programmes are promising strategies to reduce the risk of violence against children, but evidence of the effectiveness of combining such programmes is lacking for families in low-and middle-income countries with children over two years of age. This study examined the effectiveness of a locally adapted parenting programme delivered as part of a government CCT system to low-income families with children aged two to six years in Metro Manila,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…We found six recent reviews and meta-analyses of parenting programs for caregivers of young children to prevent violence and child behavior problems [ 43 , 44 , 45 , 46 , 47 , 48 ]. Furthermore, we found 17 recent randomized controlled trials of 11 parenting programs implemented in LMICs targeted toward young children, which were effective in reducing VAC, key drivers of VAC, and child behavior problems (see Table 2 ) [ 15 , 23 , 24 , 25 , 26 , 28 , 29 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found six recent reviews and meta-analyses of parenting programs for caregivers of young children to prevent violence and child behavior problems [ 43 , 44 , 45 , 46 , 47 , 48 ]. Furthermore, we found 17 recent randomized controlled trials of 11 parenting programs implemented in LMICs targeted toward young children, which were effective in reducing VAC, key drivers of VAC, and child behavior problems (see Table 2 ) [ 15 , 23 , 24 , 25 , 26 , 28 , 29 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Parenting for Lifelong Health program for young children was originally developed by integrating common evidence-based program components within the local cultural context in South Africa [ 21 ]. Subsequent testing in randomized controlled trials in South Africa, Thailand, and Philippines demonstrated positive impacts on reduced violence against children and child behavior problems, improved caregiver mental health and positive parenting, and reduced intimate partner violence, the latter in the Philippines [ 22 , 23 ]. Similarly, the Parenting for Lifelong Health program for parents and adolescents was developed in rural South Africa and then tested in a cluster randomized controlled trial showing positive effects across a range of family outcomes [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Parenting for Lifelong Health (PLH) programmes are now being implemented in over 25 countries in Africa, Asia, and Southeastern Europe. To date, four randomised controlled trials (RCTs) have examined the effectiveness of PLH-YC-two in South Africa, one in the Philippines, and one in Thailand (Gardner et al, forthcoming;Lachman et al, 2017Lachman et al, , 2021Ward et al, 2020). These studies found improved positive parenting and child behaviour, while reducing family violence.…”
Section: Parenting For Lifelong Healthmentioning
confidence: 99%